2013
DOI: 10.1523/jneurosci.3870-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

PI3K-Akt Signaling Activates mTOR-Mediated Epileptogenesis in Organotypic Hippocampal Culture Model of Post-Traumatic Epilepsy

Abstract: mTOR is activated in epilepsy, but the mechanisms of mTOR activation in post-traumatic epileptogenesis are unknown. It is also not clear whether mTOR inhibition has an antiepileptogenic, or merely anti-convulsive effect. The rat hippocampal organotypic culture model of post-traumatic epilepsy was used to study the effects of long term (four weeks) inhibition of signaling pathways that interact with mTOR. Ictal activity was quantified by measurement of lactate production and electrical recordings, and cell deat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
82
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(93 citation statements)
references
References 43 publications
8
82
1
Order By: Relevance
“…Importantly, the organotypic hippocampal slice culture can be maintained stably for weeks in vitro, which make them applicable for epileptogenesis studies. Under standard culture conditions and in the absence of additional convulsant manipulations, spontaneous electrographic activity that closely resembles interictal spikes develops in the first week in vitro, and seizure-like epileptiform activity develops during the second week in vitro (DyhrfjeldJohnsen et al 2010;Berdichevsky et al 2012Berdichevsky et al , 2013. The seizure-like, but not spike-like activities, are suppressed by standard anticonvulsants, such as phenytoin, corresponding to the effects of these drugs in human epilepsy patients (Berdichevsky et al 2012).…”
Section: In Vitro Models Of Epileptogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, the organotypic hippocampal slice culture can be maintained stably for weeks in vitro, which make them applicable for epileptogenesis studies. Under standard culture conditions and in the absence of additional convulsant manipulations, spontaneous electrographic activity that closely resembles interictal spikes develops in the first week in vitro, and seizure-like epileptiform activity develops during the second week in vitro (DyhrfjeldJohnsen et al 2010;Berdichevsky et al 2012Berdichevsky et al , 2013. The seizure-like, but not spike-like activities, are suppressed by standard anticonvulsants, such as phenytoin, corresponding to the effects of these drugs in human epilepsy patients (Berdichevsky et al 2012).…”
Section: In Vitro Models Of Epileptogenesismentioning
confidence: 99%
“…posed as one model for screening of antiepileptogenic therapies, and initial studies with mTOR antagonists have supported the utility of this preparation in rapidly dissecting complex signaling pathways (Berdichevsky et al 2013). However, it will be important to subject the findings obtained in vitro to subsequent in vivo replication studies, particularly in cases in which complex in vivo results have been obtained (Lew and Buckmaster 2011;Guo et al 2013).…”
Section: A Pitkä Nen Et Almentioning
confidence: 99%
“…Enhanced mTOR activation has been linked to mouse models of infantile spasms (see Raffo et al 2011) and seizures induced in a hypoxia model lead to enhanced expression of genesencoding components of the mTOR pathway (Theilhaber et al 2013). There is PI3K-and Akt-dependent mTOR activation in a rat hippocampal organotypic culture model of posttraumatic epilepsy, and inhibition of PI3K, mTOR, or both (using a dual inhibitor) mitigated ictal activity and cell death (Berdichevsky et al 2013). Enhanced mTOR activation is found in human temporal lobe epilepsy specimens (Sha et al 2012;Sosunov et al 2012), and a recent study showed enhanced mTOR signaling in a variety of epilepsy-associated structural lesions including mesial temporal sclerosis, FCD type IIIa, FCD type IIIc, and Rasmussen's encephalitis (Liu et al 2014).…”
Section: Mtor Malformations and Epileptogenesis: Distinct Mechanistmentioning
confidence: 99%
“…Lactate dehydrogenase (LDH) is released into culture medium after plasma membrane loses its integrity,27, 28, 29 and its concentration is correlated with cell death in cultures. We then demonstrated that this preparation and lactate and LDH assays can be used to evaluate anticonvulsant efficacy, using phenytoin and manipulation of mTOR pathway as examples 30, 31. We now show the utility of this in vitro model of chronic epilepsy as a first, blinded, moderate throughput stage for drug screening.…”
Section: Introductionmentioning
confidence: 84%
“…The use of organotypic hippocampal cultures, where epileptogenesis occurs on a compressed time scale,23, 24 and where seizures and seizure‐induced cell death can be easily quantified with biomarker assays,30, 31 allowed us to circumvent the throughput limitations of in vivo chronic epilepsy models 4. Thus, we were able to screen 140 compounds and combinations of compounds, in over 400 separate drug‐concentration experiments, and identify over 40 hits.…”
Section: Discussionmentioning
confidence: 99%